Percepción de los usuarios del servicio de agua potable en Tamshiyacu. Distrito de Fernando Lores. Loreto 2021 - Ochoa Jaramillo, Silvia (2024)
This research was carried out to distinguish the perception that domestic users have of the drinking water service in Tamshiyacu, district of Fernando Lores in the year 2023, it was from a quantitative, descriptive, cross-sectional approach, using the survey as a data collection tool. The sample was obtained from a population of 4 908 households distributed in four areas of Tamshiyacu by applying a non-probabilistic convenience sampling of 358 households to a head of household. With the data obtained, a data matrix was created using SPSS v. 27, the results of which were analyzed in three parts: perception of the drinking water service, quality and satisfaction, where 88% of the population is supplied by the drinking water distribution service, which reaches their homes in adequate quantity (76%), 68% is of good quality, the smell, taste, color of the water is also adequate according to their perception, 94%, 66% and 93% respectively. Finally, they perceive a degree of satisfaction of 90%, for the quantity and quality of water they consume they also reflect 80% and 64% respectively. Likewise, 60% indicate that they are satisfied with the payment of the water service they consume.